Defining of the characteristic ways for workpieces positioning in the fixture - Rodić, Milorad (Journal of Production Engineering, 1991)
Part of developed system for automatic fixture design is module for designing of workpieces positioning in the fixture. The first step in the scope of this module is defining of the characteristic ways for workpieces positioning. In the paper, the characteristic ways for workpieces positioning in the fixtures are shown. In spite of that, six points rule is respected in depedence on the form of the basic support surface. The most frequent basic support surfaces are observed: feat surface, cylindrical surface - external and internal, conical surface - external and internal and spherical surface - external and internal. Appropriate surfaces for six levels of freedom toking away is given too. All of that is shown in tables. Verification is done observing concrete example.